2005
DOI: 10.1128/jvi.79.6.3615-3626.2005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Cytomegalovirus ori Lyt Sequence Requirements in the Context of the Viral Genome

Abstract: During the lytic phase of infection, replication of herpesvirus genomes initiates at the lytic origin of replication, oriLyt. Many herpesviruses harbor more than one lytic origin, but so far, only one oriLyt has been identified for human cytomegalovirus (HCMV). Evidence for the existence of additional lytic origins of HCMV has remained elusive. On the basis of transient replication assays with cloned viral fragments, HCMV oriLyt was described as a core region of 1.5 kbp (minimal oriLyt) flanked by auxiliary se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 58 publications
0
60
0
Order By: Relevance
“…The recombinant viruses (RV) used in this study were derived from the bacterial artificial chromosome (BAC)-cloned genome (pHB5) of the HCMV laboratory strain AD169 (6). The HCMV BAC pHG contains an enhanced green fluorescent protein (EGFP) gene in the unique short region and lacks the open reading frames (ORFs) UL1 to UL10 (UL1-10), with only one Flp recognition target (FRT) site retained at this position (9). The BAC pHD corresponds to pHB5 with the UL1-10 locus deleted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant viruses (RV) used in this study were derived from the bacterial artificial chromosome (BAC)-cloned genome (pHB5) of the HCMV laboratory strain AD169 (6). The HCMV BAC pHG contains an enhanced green fluorescent protein (EGFP) gene in the unique short region and lacks the open reading frames (ORFs) UL1 to UL10 (UL1-10), with only one Flp recognition target (FRT) site retained at this position (9). The BAC pHD corresponds to pHB5 with the UL1-10 locus deleted.…”
Section: Methodsmentioning
confidence: 99%
“…Primers used to disrupt the UL52 gene in the HCMV BACs were UL52-ko.for (5Ј-GCGGCCGCCTCATACCAGGTAA ATCCTCAACACCCCGCCAAGAAAAGTGCCACCTGCAGAT-3Ј) and UL52-ko.rev (5Ј-TTGGTGACGCGGATGTTGCCGGCGCACTGCGGGTCG CAGAACAGGAACACTTAACGGCTGA-3Ј), and plasmid pOri6K-F5 served as a template. pOri6K-F5 encodes a knR marker flanked by mutant FRT sites that do not interact with the wild-type FRT sites (9). Subsequent excision of the FRT-flanked KnR marker was done in E. coli via Flp recombinase expressed by plasmid pCP20 as described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…Having shown that pUL77-mGFP and pUL93 are capsid constituents, we next asked whether these proteins may play a role in HCMV genome encapsidation. To this end, either UL77 or UL93 was deleted from the HG genome, an AD169 strain-based EGFP-expressing HCMV BAC (31). We first tested if genome cleavage is still carried out after disruption of UL77 or UL93.…”
Section: Generation Of Hcmv Mutants Expressing a Ul77-mgfp Fusion Promentioning
confidence: 99%
“…pHB5 denotes the original AD169 BAC, and pHG represents an enhanced green fluorescent protein (EGFP)-expressing pHB5 derivative (31). hTERT-RPE-1 cells (Clontech) were propagated as described previously (29).…”
Section: Viruses and Cellsmentioning
confidence: 99%
“…Thus, it is speculated that HCMV establishes an environment in which it hijacks the cellular DNA replication machinery to benefit its own genome replication. HCMV DNA replication initiates from the replication origin oriLyt [24][25][26] and is thought to take place at sites near the nuclear domain 10 (ND10), which is disrupted as the replication progresses [27,28]. Subsequently, HCMV replication sites are enlarged to form globular replication compartments that eventually fill the nucleus at late stage [19,29,30].…”
Section: Introductionmentioning
confidence: 99%